Pemodelan Harga Saham Menggunakan Geometric Brownian Motion - Ul Hasanah, Fitri Rahmah; Putri, Darvi Mailisa (UIN Imam Bonjol Padang, 2022)
Stocks are something that is still interesting to this day to be discussed. Because the price tends to fluctuate, it is necessary to make predictions for the future in order to reduce losses for investors. Geometric Brownian Motion is a model for predicting stock prices by conducting a study through stock return data obtained. Stock return data is required to meet the assumptions of Geometric Brownian Motion. After that, the average value and volatility of the stock return data of PT. Aneka Tambang Tbk. from January 04th to June 30th 2021 amounted to Â -0,002376925 and 0,0212161. Through stock return parameters and data generation with a standard normal distribution, a model that is very close to the actual stock price data is obtained.